Does Social Media Use and Adverse Life Events Related to Depression? A Population-based Study Using Negative Binomial Regression - Syukrilla, Wara Alfa (Universitas Muhammadiyah Purwokerto, 2023)
The impact of social media use on mental health remains a contentious issue, with varying evidence reported across studies. Concurrently, the prevalence of adverse life events, a significant global social concern, has been increasing. This study investigates the influence of social media use and adverse life events on depression symptoms among individuals in Indonesia. Using a nationally representative sample of 29,793 participants from the Indonesian Family Life Survey Wave 5, depression levels were assessed via the Center for Epidemiologic Studies Depression (CES-D) scale. To account for the overdispersed nature of count data, a negative binomial regression model was utilized to analyze the effects of social media use and adverse life events on depression. The findings reveal that both social media use and the frequency of adverse life events are significantly associated with higher rates of depressive symptoms. Additionally, the study indicates that depression rates are more pronounced among females and younger individuals compared to males and older adults. Educational programs should be designed to raise awareness about the potential mental health risks associated with excessive social media use. Policy makers should also consider integrating mental health support into disaster response plans to better support individuals experiencing adverse life events.